Capacitive pressure-sensitive composites using nickel–silicone rubber: experiments and modeling. (9th June 2017) - Fan, Yuqin; Liao, Changrong; Liao, Ganliang; Tan, Renbing; Xie, Lei
Abstract: Capacitive pressure (i.e., piezo-capacitive) sensors have manifested their superiority as a potential electronic skin. The mechanism of the traditional piezo-capacitive sensors is mainly to change the relative permittivity of the flexible composites by compressing the specially fabricated microstructures in the polymer matrix under pressure. Instead, we study the piezo-capacitive effect for a newly reported isotropic flexible composite consisting of silicone rubber (SR) and uniformly dispersed micron-sized conductive nickel particles experimentally and theoretically. The Young's modulus of the nickel-SR composites (NSRCs) is designed to meet that of human skin. Experimental results show that the NSRCs exhibit remarkable particle concentration dependent capacitance response under uniaxial pressure, and the NSRCs present a good repeatability. We propose a mathematical model at particle level to provide deep insights into the piezo-capacitive mechanism, by considering the adjacent particles in the axial direction as micro capacitors connected in series and in parallel on the horizontal plane. The piezo-capacitive effect is determined by the relative permittivity induced by the particles rearrangement, longitudinal interparticle gap, and deflection angle of micro particle capacitors under pressure. Specifically, the relative capacitance of NSRC capacitor is deduced to be product of two factors: the degree of particle rearrangement, and the relative capacitance of a micro capacitor with the average longitudinal gap. The proposed model well matches and interprets the experimental results.